Learning Achievements in Maintenance of ABS (Antilock Braking System) Brake System Through PBL - Mushthofaina Al Akhyar, Zidane; Widjanarko, Dwi; Sutopo, Yeri (Journal of Vocational and Career Education, 2024)
The conventional approach of current learning media and the limited utilization of Android technology among students as a learning medium highlight the need for improvements and updates in how information is delivered from teachers to students. Transitioning from traditional methods to more modern approaches, particularly by leveraging existing technology, is essential. This study aims to develop Android-based interactive multimedia using the Problem-Based Learning (PBL) model to enhance learning achievements in the maintenance of ABS (Antilock Braking System) brake systems. It evaluates the feasibility and the improvement in learning outcomes among students in the Light Vehicle Engineering Department at SMK Muhammadiyah 2 Semarang in cognitive, affective, and psychomotor domains. The research employs the ADDIE development model, which includes Analysis, Design, Development, Implementation, and Evaluation. The experimental design used is a Pretest-Posttest Control Group Design. The subjects consist of 60 eleventh-grade students from the Light Vehicle Engineering Department, divided into control and experimental groups. The results of the feasibility assessment by media and material experts are 83.20% (“Feasible”) and 88.78% (“Highly Feasible”), respectively. Improvements in learning outcomes are reflected in the N-Gain test results, with the experimental group achieving an average score of 0.4619, categorized as “Moderate,” while the control group achieved an average score of 0.2588, categorized as “Low.” Based on the N-Gain calculations, it can be concluded that the use of Android-based multimedia through the Problem-Based Learning model in ABS brake system maintenance materials is “Effective”.